«Culturas y prácticas políticas en la España contemporánea (siglo XVIII-1936)» - autor, Sin (Cuadernos de Historia Moderna, 2003)
Attending the aims of the New Political History, three main subjects were discussed in this seminar: the concept of politics in Eighteenth century, the birth of new structures of power in Nineteenth century and the new political strategies in modern society.